Cognitive Radio Networks and Spectrum Sensing: A Review - Talajiya, Preet Hitesh; Gangurde, Aniket Pramod; Ragavendran, U; Murali, Hariharan (International Journal of Online and Biomedical Engineering (iJOE), 2020)
The wireless spectrum demand is at a constant rise in contrast to its scarcity. Cognitive Radio Networks(CRN’s) as a notion was first brought into the light to tackle this issue. A CRN is an intelligent network that dynamically changes its characteristics through the process of Spectrum Sensing and adapts to the convenience of the environment it is in. This article presents a basic overview of what CRN’s are. The major contributions of this paper lie in a comparative study of CRN’s and Spectrum Sensing in recent years as well as its main challenges and applications. This review shall help current and new researchers in the field to look for future outlooks and give them a basic run-through of CRN’s and Spectrum Sensing and their characteristics.